2020
DOI: 10.1371/journal.pone.0231079
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of accessibility to emergency rooms by dynamic population from mobile phone data: Geography of social inequity in South Korea

Abstract: Accessibility of emergency medical care is one of the crucial factors in evaluating national primary medical care systems. While many studies have focused on this issue, there was a fundamental limit to the measurement of accessibility of emergency rooms, because the commonly used census-based population data are difficult to provide realistic information in terms of time and space. In this study, we evaluated the geographical accessibility of emergency rooms in South Korea by using dynamic population counts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
1
10
0
2
Order By: Relevance
“…Recently, a noticeable trend is that more types of data, such as data based on location-based service (LBS), have been combined with accessibility analysis to correlate actual population flow and distance decay effect, etc. [26,32] Due to the COVID-19 pandemic, spatial accessibility assessments of COVID-19 patients to healthcare facilities were studied by researchers [33][34][35]. In these studies, it was believed that people living in areas of dense population or on the margins were disproportionately disadvantaged in terms of the access to medical facilities and healthcare [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a noticeable trend is that more types of data, such as data based on location-based service (LBS), have been combined with accessibility analysis to correlate actual population flow and distance decay effect, etc. [26,32] Due to the COVID-19 pandemic, spatial accessibility assessments of COVID-19 patients to healthcare facilities were studied by researchers [33][34][35]. In these studies, it was believed that people living in areas of dense population or on the margins were disproportionately disadvantaged in terms of the access to medical facilities and healthcare [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Based on data of the AHA's GWTG-R, Merchant et al reported no statistically significant difference between incidence of IHCA in urban and rural areas [25]. This difference is due to the medical accessibility resulting from the geographical factors and relatively unforced health care delivery system in the nation [26].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have pointed out that although census-based population data is the most meaningful representation of the social and economic status of people, it is hard to reflect dynamic spatial-temporal patterns of people from this data alone. Specifically, the census-based population represents the number of people who are registered in a given district, and it is difficult to capture the human dynamics that can be reflected by mobile-based population patterns ( Baker et al, 2017 ; Yun et al, 2020 ). Also, static census-based populations are collected every 5 to 10 years, whereas mobile-based population information captures real-time information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, static census-based populations are collected every 5 to 10 years, whereas mobile-based population information captures real-time information. Mobile phone-based population data was considered to analyze actual demands for public facilities, and the human dynamics of the spatial-temporal characteristics of people ( Jung & Nam, 2019 ; Jo et al, 2020 ; Yun et al, 2020 ). Gender information from mobile-based floating population data was used to analyze gender equality with regard to the use of urban space in Seoul ( Jo et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation